Aristocratic liberalism : the social and political thought of Jacob Burckhardt, John Stuart Mill, and Alexis de Tocqueville /: the social and political thought of Jacob Burckhardt, John Stuart Mill, and Alexis de Tocqueville. (2017) - Kahan, Alan S
No abstract available